Differences in health visiting contacts for children of mothers with and without a history of adversity-related hospital admissions in England (2018/19 to 2019/20): an analysis of novel linked community health and hospital data. - Mc Grath-Lone, Louise; Woodman, Jenny; Clery, Amanda; Liu, Mengyun; Bunting, Catherine; Harron, Katie (International Journal of Population Data Science, 2024)
Objective Explore differences in children’s contact with health visiting (HV) services by pre-birth exposure to maternal adversity. Approach For the first time, we linked the Community Services Dataset (CSDS), which records HV contacts for children in England from 1 April 2018 to 31 March 2020, to Hospital Episode Statistics (HES) which contains births and mothers’ hospital admissions in the preceding 3 years. We used admissions that included ICD-10 codes related to mental health, substance use and violence to identify children born to mothers with a history of adversity. We compared characteristics of children’s HV contacts (i.e. number, mode, location, duration) stratified by maternal adversity. Results Overall, 85.2% of 626,478 children in CSDS linked to a birth record in HES. Among children receiving HV contacts, 11.7% were exposed to maternal adversity: 11.1% mental health, 1.3% substance use, 0.4% violence. Children with maternal adversity had more HV contacts than other children (mean = 3.8 vs 2.7, p<0.001). There were no differences in contact mode (i.e. face-to-face or phone) for children with maternal adversity compared to others, but their contacts were longer (44.5% lasting >30 minutes vs 35.1%, p<0.001) and more likely to be at home (56.3% vs 47.8%, p<0.001). Conclusions HV services respond in different ways to children with and without pre-birth exposure to serious maternal adversity, reflecting the “proportionate universalism” that underpins HV services in England. Implications The differential service response for vulnerable children may require additional resources (e.g. staff, training) which should be considered when designing and funding HV services.